2015
DOI: 10.1016/j.chemosphere.2015.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Current exposure of Italian women of reproductive age to PFOS and PFOA: A human biomonitoring study

Abstract: Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) concentrations were determined in serum samples collected in 2011-2012 from 549 nulliparous Italian women of reproductive age who resided in six different Italian Regions. Assessment of exposure to perfluorinated compounds was part of a large human biomonitoring study (Project Life Plus "Womenbiopop") that aimed at examining the exposure of women of reproductive age to priority organic pollutants. The median concentrations of PFOS and PFOA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…The reports of the AMAP and HBM4EU (with a good z-score) intercalibration exercises (https://www.hbm4eu.eu; AMAP Ring Exercise Test for Persistent Organic Pollutants in Human Serum https://www.inspq.qc.ca/en/ctq/eqas/amap/description [ 10 , 15 18 ]) support the findings of this study.…”
Section: Data Availabilitysupporting
confidence: 85%
See 1 more Smart Citation
“…The reports of the AMAP and HBM4EU (with a good z-score) intercalibration exercises (https://www.hbm4eu.eu; AMAP Ring Exercise Test for Persistent Organic Pollutants in Human Serum https://www.inspq.qc.ca/en/ctq/eqas/amap/description [ 10 , 15 18 ]) support the findings of this study.…”
Section: Data Availabilitysupporting
confidence: 85%
“…We ordinarily use the method hereafter described for the analysis of serum samples within the framework of various national and international projects and in interlaboratory comparison exercises [ 10 , 14 – 18 ], Ring Exercise Test for Persistent Organic Pollutants in Human Serum https://www.inspq.qc.ca/en/ctq/eqas/amap/description [ 19 ]. Results obtained by our laboratory in the interlaboratory comparison exercises are reported in detail in supplementary data 2.…”
Section: Methodsmentioning
confidence: 99%
“…Their toxic effects on the human body have been confirmed in numerous mammalian toxicology studies and in general population epidemiological investigations [ 7 , 8 , 9 ]. Therefore, the occurrence of PFAAs in humans has attracted great attention in recent years [ 7 , 10 , 11 , 12 ], as have the exposure routes (water, air, house dust, and food) [ 13 ]. Comparing the main sources of human exposure, D’Hollander et al [ 14 ] found that food consumption is the most important.…”
Section: Introductionmentioning
confidence: 99%
“…Perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) are two of the most widely used PFCs. PFOA and PFOS have already been considered as emerging persistent organic pollutants [ 8 ]. The distribution of PFOA and PFOS in the environment has increased universally in recent years [ 9 ] and their accumulation and toxic effects have become serious issues to be addressed [ 10 ].…”
Section: Introductionmentioning
confidence: 99%